Variability of the content of active substances during Achillea collina Rchb. Alba ontogenesis - K. Karlová; K. Petříková (Horticultural Science, 2005)
The fluctuation of essential oil, flavonoid and tannin content in Achillea collina Rchb. Alba (flos and herba millefolii) during ontogenesis was studied in this paper. Ten developmental stages of plants - from the beginning of flower differentiation to ripe seed stage - were tested for 3 years. The essential oil content was found to range between 0.4 and 1.6% of dry material and it was statistically significantly (one-factor analysis of variance; α = 0.05) influenced by developmental stage, harvested part of the plant and also by seasonal climatic conditions. The flavonoid content was influenced only by developmental stage and not by the type of yarrow drug or season. Its values ranged from 0.7 to 6.0% of dry material and it had a clear decreasing tendency during the plant ripening. Compared to flavonoids tannin production showed a reverse trend in yarrow. Their content was 0.3-1.0% and it increased during seed maturing. However differences between tannin contents during yarrow ontogenesis are not so dramatic and the influence of harvested part and season is also disputable. Comparison of the content of active substances in the drug from one- and six-years old yarrow plants did not indicate any differences due to age. Developmental stage V, beginning of flowering, can be recommended to producers as an optimum harvest stage because in this period the drug has the highest essential oil content in relation to plant mass yield and also to flavonoid and tannin contents.